2021
DOI: 10.3390/polym13091514
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Rifampicin Loaded Alginate–Gelatin Biocomposite Microfibers

Abstract: Various systematic phases such as inflammation, tissue proliferation, and phases of remodeling characterize the process of wound healing. The natural matrix system is suggested to maintain and escalate these phases, and for that, microfibers were fabricated employing naturally occurring polymers (biopolymers) such as sodium alginate, gelatin and xanthan gum, and reinforcing material such as nanoclay was selected. The fabrication of fibers was executed with the aid of extrusion-gelation method. Rifampicin, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…FTIR analyses of PCL NPs, PCL−RFP NPs and RFP were observed in the range of 4000 to 400 cm −1 as shown in Figure 2A. In pure drug (RFP), the CH bond, C=O stretch and C−H bending occur at 2936, 1653, and 968 cm −1 , respectively [20] . Typical IR peaks of PCL were observed in both PCL NPs and PCL−RFP NPs.…”
Section: Resultsmentioning
confidence: 94%
“…FTIR analyses of PCL NPs, PCL−RFP NPs and RFP were observed in the range of 4000 to 400 cm −1 as shown in Figure 2A. In pure drug (RFP), the CH bond, C=O stretch and C−H bending occur at 2936, 1653, and 968 cm −1 , respectively [20] . Typical IR peaks of PCL were observed in both PCL NPs and PCL−RFP NPs.…”
Section: Resultsmentioning
confidence: 94%
“…For example, TB treatments include a two-month intensive therapy with different combinations of the first-line agents RIF, ISN, PYR and ETB, followed by another four months of RIF and ISN administration [ 57 ]. It was found that RIF could be applied for wound healing as well [ 58 ], and it was also explored to prevent the formation of biofilms [ 43 ]. There have been reports emphasizing that RIF has a neuroprotective function [ 59 ] and a therapeutic role in neurodegenerative disorders [ 60 , 61 ], including Alzheimer’s disease [ 62 ], as well as an ability to increase the accumulation of anticancer drugs in multidrug-resistant cancer cells [ 63 ], to cleavage or to bind to DNA [ 64 ], which may contribute to RIF anti-cancer activity.…”
Section: Rifamycins—properties and Clinical Treatmentmentioning
confidence: 99%
“…Owing to their flexibility and soft nature, microfibers are used for drug delivery applications. In 2021, Sharma et al [ 58 ] described the fabrication of RIF-loaded microfibers by the ionotropic gelation method, starting with the naturally occurring biopolymers sodium alginate and gelatin, to which xanthan gum and nanoclay were added to enhance the mechanical strength of the fibrous structure. These biocomposite microfibers could be used for controlled and prolonged RIF release and as wound dressing material.…”
Section: Rifamycins Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations